Determination of Sustainable Consumption Behaviors of Pre-service Science Teachers Using the Theory of Planned Behavior: A Case of Fast-Food - Kibar Sungur Gül; Huseyin Ates (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Individuals’ sustainable consumption has a substantial effect on the environment. In particular, fast-food consumption is an important obstacle to a sustainable life. Therefore, understanding antecedents of fast-food consumption behavior helps to develop sustainable education interventions. The study aims to examine factors affecting fast food consumption behaviors within the framework of the sustainability framework using the theory of planned behavior. The sample data of 270 participants were from pre-service science teachers. The data of the study were collected several scales. A belief scale was developed by researchers. Other scales were adapted from the previous studies. The analysis was performed using hierarchical multiple regression analysis. The results revealed that the conceptual model explained 19 % of the variance in intention and 33 % of the variance in behavior. Besides, the proposed relationships among the constructs within the model were broadly supported. Further, intention was found to be a significant mediating variable. Finally, the study provides important theoretical and practical implications as well as suggestions for future researchers.